Successful use of ofatumumab in two cases of early-onset juvenile SLE with thrombocytopenia caused by a mutation in protein kinase C δ - Linda Lei; Sabina Muhammad; Muthana Al-Obaidi; Neil Sebire; Iek Leng Cheng; Despina Eleftheriou; Paul Brogan (BMC, 2018)
Abstract Background We previously described an endogamous Pakistani kindred in whom we identified a novel homozygous missense mutation in the PRKCD gene encoding for protein kinase C δ (PKCδ) as a cause of monogenic systemic lupus erythematosus (SLE). PKCδ has a role in the negative regulation of B cells. Given the nature of the disease, a logical targeted therapeutic approach in these patients is B cell depletion. Indeed, the 3 siblings all had a marked clinical response and resolution of symptoms with rituximab, although 2 of the siblings had severe reactions to rituximab thus precluding further treatment with this. We therefore describe the first successful use of ofatumumab for this rare form of monogenic SLE. Case presentation All three affected siblings presented with SLE before the age of 3-years with lethargy, intermittent fever, thrombocytopenia, cutaneous involvement, alopecia, and hepatosplenomegaly. Tubulointerstitial nephritis was also present in 1 of the siblings. Homozygosity mapping followed by whole exome sequencing identified a homozygous missense mutation in PRKCD (p.Gly432Trp), subsequently confirmed by Sanger sequencing to be present in all 3 siblings. All 3 patients were initially treated with rituximab, however 2 of the siblings developed severe infusion-related reactions. For subsequent disease flare in these individuals we therefore used an alternative B cell depleting agent, ofatumumab (300 mg/1.73m2 on day 1; 700 mg/1.73m2 on day 15). This resulted in marked clinical improvement in both patients. To the best of our knowledge, this is the first report describing the successful use of ofatumumab for PKCδ deficiency. Conclusions PKCδ deficiency causes a monogenic form of SLE which responds well to B cell depletion. Ofatumumab is also likely to have a therapeutic role for sporadic juvenile SLE (jSLE) patients intolerant of rituximab.